Surface decontamination of spinach by intense pulsed light treatments: impact on quality attributes - Agüero, Maria Victoria (2016)
Intense pulsed light (IPL) treatments constitute an emerging non-thermal technology proposed to decontaminate food surfaces. In this study, the bactericidal effect of IPL against Listeria innocua and Escherichia coli inoculated on spinach leaves was evaluated and mathematically modeled. Also, the impact of IPL treatments (20 and 40 kJ m−2) on headspace gas composition, microbial quality, antioxidant properties and color of spinach was assessed immediately after treatment and during refrigerated storage. IPL treatments were effective for reducing the naturally-occurring microbial load on the raw material by 0.4–2.2 Log CFU g−1, depending on the applied fluence. IPL treatments also reduced the growth rates of microbial populations through storage. Changes in the package headspace composition were significantly affected by IPL treatments. In-package production of CO2 increased at a higher rate than for untreated spinach leaves, while O2 concentrations decreased. Total polyphenolic content and antioxidant capacity of spinach exhibited significant increases in the range of 5–10% and 32–34% for the samples treated with 20 or 40 kJ m−2, respectively. Despite these initial increases, treated spinach leaves presented an accelerated decrease in these quality indicators during refrigerated storage. At the end of storage, IPL-treated samples presented a slightly lower phytochemical quality but significant better microbial quality than control samples.